2011
DOI: 10.1016/j.scitotenv.2011.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Daily urinary excretion of uranium in members of the public of Southwest Nigeria

Abstract: The main aim of this study was to determine and evaluate urinary excretion values of uranium in members of the public of Southwest Nigeria living in areas of low environmental uranium. As several uranium mines are running in Nigeria and the operations could be a risk of contamination for the workers as well as for the members of the public, biomonitoring of urine could provide information about the exposure to uranium for the subjects. Therefore, baseline values of uranium in urine are needed from subjects liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The ICRP uranium model (ICRP, 1995a,b) also predicted such an increase under conditions of a continuous level of intake. In contrast, Hoellriegl et al, (2011) and Oeh et al, (2007) concluded that there was no dependency of uranium excretion with age, which is consistent with our conclusion.…”
Section: Urine Samplessupporting
confidence: 91%
See 1 more Smart Citation
“…The ICRP uranium model (ICRP, 1995a,b) also predicted such an increase under conditions of a continuous level of intake. In contrast, Hoellriegl et al, (2011) and Oeh et al, (2007) concluded that there was no dependency of uranium excretion with age, which is consistent with our conclusion.…”
Section: Urine Samplessupporting
confidence: 91%
“…Urine monitoring is the preferred method to determine human exposure to soluble { PAGE \* MERGEFORMAT } uranium since the amount excreted per day via urine is related to the total level of uranium in the body (Hoellriegl et al, 2011). In order to make an assessment on an individual's possible exposure, knowledge of background uranium levels is indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the wide age range of participants of the included studies, studies were grouped into three groups according to the age of the participants; 2-5 years (17 studies) [26,28,36,[43][44][45] [25,26,29,36,49,53,54,63,65,67,69,81]. These cut-points were chosen based on the WHO criteria for assessing population iodine deficiency, which defines school-aged children as between 6 and 12 years of age [6].…”
Section: Discussionmentioning
confidence: 99%
“…The cut-offs used by the remaining three studies [43,48,55] were based on the distribution of volume in the sample, enabling the exclusion of extreme outliers (e.g., 4SDs below the geometric mean [48]). Of the 26 studies which reported the urine exclusion criteria, 6 did not report the number of urine samples excluded from the final analysis [25,54,[73][74][75]82]. As a result of the inconsistency in the criteria used to assess the completeness of the urine samples between studies, 23 studies (54%) scored low on the NOS quality scale [44-46, 49-51, 53-55, 57-59, 62, 63, 65, 69, 71-76, 82] ( Tables 3 and 4).…”
Section: Quality Of Studies Considered For Primary Analysismentioning
confidence: 99%
“…5.4.23 Uranium. Nigeria is a principal area for mining of U. Hollriegl et al, 126 therefore, considered it important to establish a baseline value for urine U in non-exposed Nigerian populations in order to better assess cases of environmental exposure from mining activity. They determined U in 24 h urine samples collected from adult and child volunteers in a low environmental U region of SW Nigeria.…”
Section: View Article Onlinementioning
confidence: 99%